Effect of serum 25‐hydroxyvitamin D levels on sperm quality and assisted reproductive technology outcomes for men of infertile Chinese couples. (3rd June 2020) - Chen, Yilu; Liu, Defeng; Zeng, Lin; Xu, Huiyu; Jiang, Hui; Yang, Rui; Wang, Haining; Yan, Liying; Li, Rong; Qiao, Jie; Zhi, Xu
Abstract: Introduction: Vitamin D insufficiency/deficiency is highly prevalent in China, but its effect on sperm quality and outcomes of assisted reproductive technology (ART) in men from infertile couples is not clear. This study aimed to explore the association of serum 25‐hydroxyvitamin D (25OHD) levels and semen parameters, as well as ART outcomes for men from infertile couples. Materials and methods: This study recruited 1308 men from infertile couples who attended the Reproductive Medicine Center of Peking University Third Hospital for first time from February to August 2019 (NCT03804294). Reproductive hormones levels, semen parameters, and clinical outcomes of ART were compared between vitamin D‐deficient group (serum 25OHD ≤ 10 ng/mL), insufficient group (serum 25OHD 10‐20 ng/mL), and sufficient group (serum 25OHD ≥ 20 ng/mL). Results: We found 27.7% of participants were vitamin D sufficient, suggesting high prevalence of vitamin D insufficiency/deficiency in China. Reproductive hormone levels were similar between the three groups. The total number of morphologically normal spermatozoa was significantly different between the three groups in all participants, impaired semen quality subgroup, and normozoospermia subgroup ( P  < .05) with the adjustment of confounders (age, BMI, alcohol consumption, cigarette smoking, and physical exercise). The percentage of normal sperm morphology significantly increased with elevated serum 25OHD levels in all participants and the participants with impaired semen quality ( P  < .05), and the total sperm count showed significant difference in participants with impaired semen quality ( P  = .026). For routine in vitro fertilization and intracytoplasmic sperm injection cycles, there were no differences in fertilization rate, top‐quality embryo rate, biochemical pregnancy rate, and clinical pregnancy rate between serum 25OHD < 20 ng/mL and serum 25OHD ≥ 20 ng/mL groups. Conclusions: Males of infertile couples with higher serum 25OHD levels exhibit better results in sperm morphology, and serum 25OHD levels may contribute to total sperm number in participants with impaired semen quality, but show no effects on the ART outcomes.